Late Outcomes of Infants Supported by Extracorporeal Membrane Oxygenation Following the Norwood Operation. (January 2015) - Alsoufi, Bahaaldin; Wolf, Michael; Botha, Phil; Kogon, Brian; McCracken, Courtney; Ehrlich, Alexandra; Kanter, Kirk; Deshpande, Shriprasad
Background: Hospital survival for infants who require extracorporeal membrane oxygenation (ECMO) following the Norwood operation is 30% to 60%. However, little is known about late outcomes of hospital survivors and their ability to progress through subsequent palliative stages. Methods: Between 2002 and 2012, 38 (13.4%) of the 284 neonates with hypoplastic left heart syndrome or other single ventricle variants received ECMO support following Norwood. We examined factors affecting hospital death and compared postdischarge events between hospital survivors who received postoperative ECMO (n = 16 of 38) and a control of hospital survivors who did not receive ECMO (220 of 246). Results: Unplanned cardiac reoperation was the only predictor of postoperative ECMO requirement. Overall, 22 (58%) of the 38 patients were weaned from ECMO support and 16 (42%) of the 38 survived to hospital discharge. The ECMO duration was a significant factor for hospital mortality (odds ratio = 1.52 per 1-day increase [1.03-2.24], P = .035). Following discharge, 15 (94%) of the 16 underwent Glenn and 1 (6%) of the 16 had interstage mortality. In the control group, 194 (88%) of the 220 underwent Glenn and 26 (12%) of the 220 had interstage mortality or received transplantation ( P = .499). Following Glenn, 3 (20%) of the 15 patients had interstage mortality or received transplantation and 12 (80%) of the 15 proceeded to Fontan or were alive awaiting Fontan. In the control group, 23 (12%) of the 194 had interstage mortality or received transplantation and 171 (88%) proceeded to Fontan or were alive awaiting Fontan ( P = .357). Overall, 81% of hospital survivors were alive 5 years following discharge in both ECMO and non-ECMO groups. Conclusions: ECMO support following Norwood is associated with high probability of hospital death. Nonetheless, interstage mortality, progression to subsequent palliative stages, intermediate survival, and freedom from heart transplantation are comparable to those in patients who did not require postoperative ECMO support.